Tectonic-geomorphology of the Litang fault system, SE Tibetan Plateau, and implication for regional seismic hazard - Chevalier, Marie-Luce; Leloup, Philippe Hervé; Replumaz, Anne; Pan, Jiawei; Liu, Dongliang; Li, Haibing; Gourbet, Loraine; Métois, Marianne (Tectonophysics, 2016)
The Litang fault system (LTFS) in the eastern Tibetan Plateau has generated several large (7.5>M>7) historical earthquakes and has exhumed granitic peaks rising >1700m above the mean elevation of the plateau, despite being located within a tectonic block surrounded by highly active faults. We study horizontally offset moraine crests from the Cuopu basin and a vertically offset alluvio-glacial fan from the eastern Maoya basin. We determine a left-lateral rate of 0.09±0.02mm/yr along a slowly slipping secondary fault at Cuopu, while the main active fault at present is the normal range-front N Cuopu fault, along which we determined a left-lateral rate of 2.3±0.6mm/yr since 173ka. At Maoya fan, matching the vertical 12±1m cumulative offset with the 21.7±4.2ka fan age yields a vertical (normal) rate of 0.6±0.1mm/yr. This rate is very similar to that recently determined at the same location using low-temperature thermochronology (0.59±0.03mm/yr since 6.6±0.5Ma). Left-lateral rates along the main faults of the LTFS range between 0.9 and 2.3mm/yr at all timescales from a few years to ~6Ma. The facts that the LTFS is highly segmented and that at present, the Cuopu, Maoya and South Jawa segments are mostly normal (while the Litang and Dewu segments are left-lateral/normal), could prevent the occurrence of M>7.5 destructive earthquakes along the LTFS, as is generally assumed. However, motion on the normal faults appears to be linked with motion on the strike–slip faults, potentially allowing for exceptional larger earthquakes, and implying that the area is not experiencing pure ~NS extension but rather NW–SE left-lateral transtension. [Display omitted] •The Litang fault system (LTFS) is located in eastern Tibet•We studied horizontally offset moraine crests at Cuopu and a vertically offset fan at Maoya along the LTFS•The horizontal rate along the N Cuopu fault is ~2 mm/yr from 5.3 Ma to 29 ka•The vertical rate at Maoya is constant at ~0.6 mm/yr since 5-7 Ma•Its high segmentation, dominantly normal kinematics and low slip-rate reduce the risk of M > 7.5 earthquakes along the LTFS